2022
DOI: 10.3390/ijms23137355
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing and Its Roles in Plant Metabolism

Abstract: Plant metabolism, including primary metabolism such as tricarboxylic acid cycle, glycolysis, shikimate and amino acid pathways as well as specialized metabolism such as biosynthesis of phenolics, alkaloids and saponins, contributes to plant survival, growth, development and interactions with the environment. To this end, these metabolic processes are tightly and finely regulated transcriptionally, post-transcriptionally, translationally and post-translationally in response to different growth and developmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 178 publications
0
23
0
Order By: Relevance
“…The mechanism of pre-mRNA splicing and the process of splice site selection are fairly well understood and recent efforts have been directed toward the regulatory mechanism and function of splice variants [ 12 , 13 , 17 , 23 ]. For example, LlHSFA3B-III , a heat-induced splice variant of LlHSFA3B , has shown considerable tolerance to both salinity stress and prolonged heat treatment at 40 °C in transgenic Arabidopsis and N. benthamiana plants [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of pre-mRNA splicing and the process of splice site selection are fairly well understood and recent efforts have been directed toward the regulatory mechanism and function of splice variants [ 12 , 13 , 17 , 23 ]. For example, LlHSFA3B-III , a heat-induced splice variant of LlHSFA3B , has shown considerable tolerance to both salinity stress and prolonged heat treatment at 40 °C in transgenic Arabidopsis and N. benthamiana plants [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…AS of eukaryotic transcripts is a post-transcriptional regulatory mechanism that enables cells to produce a large diversity of proteins from a limited number of genes, thus expanding the complexity of the proteome [ 12 , 13 , 14 , 15 ]. In plants, alternatively spliced genes are involved in a range of biological processes, including regulation of metabolic pathways, intracellular signal transduction, response to biotic and abiotic stresses and control of flowering time and circadian clocks [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. With the development of high-throughput sequencing (HTS) technology, the number of AS events found in higher plants has increased far beyond expectation [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…1A). Despite the tendency of intron-retaining mRNA to be degraded via NMD (de Lima Morais and Harrison, 2010), it is becoming more clear that AS increases protein diversity (Wright et al, 2022) and is engaged in vivid metabolisms (Lam et al, 2022). We found that CRE1 int7 accumulates upon cytokinin application and decreases in cytokinin biosynthesis mutants (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative splicing is a well-known post-transcriptional regulatory mechanism of genes involved in plant metabolic pathways ( Lam et al., 2022 ). It could be a common mechanism used by plants to regulate the intracellular levels of AsA.…”
Section: Genetic Strategies For Regulation Of Asa Biosynthesismentioning
confidence: 99%